Uslûb al-Hiwâr al-Qur’âni bayna al-Muslimîn wa al-Nasâra ‘inda Badî’uzzamân Sa’îd al-Nursi - Sujiat Zubaidi Saleh (TSAQAFAH, 2014)
In order to solve some issues, the scholars’ dialogue often generates new ideas as it works to clarify the values of al-Qur’an and to enrich their understanding about it. Therefore, Nursi pointed to unite at present not only with the Muslim community and even with Christians, aside from the differences and disputes over union issues. It is possible to do so when the Muslims and the Christians refrain from their controversies among them. Nursi’s idea does not mean that he does not recognize any differences between them. There are some significant differences between the Christian and the Muslim faith, but those differences should not prevent them from the most important goal to provide new humanitarian look for human life, where God is the axis and the divine will for the moral values of this point. Nursi believes that the current religious relationship marred by erroneous thought as the result of post-modernism worldview. In fact, al-Qur’an recommended a mutual awareness of the communities that shapes them to gain a common goal in God witnesses as the divine values of this modern civilization in opposition to “clash of civilizations”, but this task needs some efforts to discuss on Quranic Dialogue. This dialogue could be undertaken well, as long as it sets out with full love and affection rather than with the fierce conflict and distress. Thus, Nursi introduced new ideas into interfaith dialogue between Muslims and Christians, to build a true civilization based on mutual relations of love.